ANALISIS ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA STUDI KASUS TERHADAP DUA ANAK DI KOTA MAKASSAR - Faizah Mangerang (Linear : Jurnal Ilmu Pendidikan, 2019)
The objectives of the study are to discover the description of children’s behaviors, factors which caused the children’s behaviors, and the handling forms on cinldren of domestic violence victims which have been conducted to date. The study is a case study research by using qualitative approach. The data sources or the main informants were the children of domestic violence victims with the initials MF and NF. The data were collected through direct observation and interview as well as documentation technique. The data were analyzed by using data reduction, data presentation, aand verification conclusion analysis. Theresults of the research showed that: (1) the description of the behaviors of the children of domestic violence victims for the first subject based on the researcher’s observation was the subject did not experience disability, behavioural disorder, mental retardation, autism, the child was too innocent, weak temperament, and he has not too dependent on adult people. While the second subject based on the researcher’s observation was the child was too dependent to adult people, (2) the factors which caused the behaviors of the children of domestic violence victims for the first subject was the subject witnessed the parent’s quarrels to each other when he has five years old and the subject was traumatized because of it, the subject was very sad in remembering the incident, physically weak/easy to get sick, preferred to be alone, the anger was unleashed to the objects around the subyect. While for the second subject, he experienced physical and psychological abuse directly from his father, the subject could not control his emotion, the subject felt that he was the superior man in the family who had to defend his mother and younger siblings from his father’s behaviors, (3) Both subject had not experienced special treatment to date whether from the family, environment, or social.